VDJtools: Unifying Post-analysis of T Cell Receptor Repertoires - Shugay, Mikhail; Bagaev, Dmitriy V; Turchaninova, Maria A; Bolotin, Dmitriy A; Britanova, Olga V; Putintseva, Ekaterina V; Pogorelyy, Mikhail V; Nazarov, Vadim I; Zvyagin, Ivan V; Kirgizova, Vitalina I; Kirgizov, Kirill I; Skorobogatova, Elena V; et al. (PLoS computational biology, 2015)
Despite the growing number of immune repertoire sequencing studies, the field still lacks software for analysis and comprehension of this high-dimensional data. Here we report VDJtools, a complementary software suite that solves a wide range of T cell receptor (TCR) repertoires post-analysis tasks, provides a detailed tabular output and publication-ready graphics, and is built on top of a flexible API. Using TCR datasets for a large cohort of unrelated healthy donors, twins, and multiple sclerosis patients we demonstrate that VDJtools greatly facilitates the analysis and leads to sound biological conclusions. VDJtools software and documentation are available at https://github.com/mikessh/vdjtools.
Keywords: mladý dospělý; Hematopoietic Stem Cell Transplantation; Twins; Receptors, Antigen, T-Cell; Child; transplantace hematopoetických kmenových buněk; výpočetní biologie; lidé; Humans; Cluster Analysis; shluková analýza; sekvenční analýza DNA; Software; mladiství; Sequence Analysis, DNA; roztroušená skleróza; Adult; software; Young Adult; dospělí; Multiple Sclerosis; receptory antigenů T-buněk; dítě; dvojčata; Computational Biology; Adolescent